2014
DOI: 10.3389/fncir.2014.00137
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical properties of BDNF-containing neurons projecting to rostral ventromedial medulla in the ventrolateral periaqueductal gray

Abstract: The periaqueductal gray (PAG) modulates nociception via a descending pathway that relays in the rostral ventromedial medulla (RVM) and terminates in the spinal cord. Previous behavioral pharmacology and electrophysiological evidence suggests that brain-derived neurotrophic factor (BDNF) plays an important role in descending pain modulation, likely through the PAG-RVM pathway. However, detailed information is still lacking on the distribution of BDNF, activation of BDNF-containing neurons projecting to RVM in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…In previous studies, it has been shown that injecting formalin into a rodent's hind paw can induce both acute spontaneous pain and long-term hyperalgesia behaviors (1)(2)(3). Long-term peripheral inflammation or tissue injury and central sensitization in the spinal cord and brain nucleus are all involved in the mediation or modulation of formalin-induced pain (4)(5)(6). There are advantages for precise clarity as to anti-nociceptive properties mediated by different mechanisms, such as peripheral anti-inflammation, and/ or central desensitization.…”
mentioning
confidence: 99%
“…In previous studies, it has been shown that injecting formalin into a rodent's hind paw can induce both acute spontaneous pain and long-term hyperalgesia behaviors (1)(2)(3). Long-term peripheral inflammation or tissue injury and central sensitization in the spinal cord and brain nucleus are all involved in the mediation or modulation of formalin-induced pain (4)(5)(6). There are advantages for precise clarity as to anti-nociceptive properties mediated by different mechanisms, such as peripheral anti-inflammation, and/ or central desensitization.…”
mentioning
confidence: 99%
“…In addition, the baroreceptor reflex is suppressed in neuropathic rats (Gemes et al, 2009), thus indicating that the baroreflex is also altered in chronic pain conditions, which suggests a more profound modification in neuronal activity induced by pain. A possible explanation for these modifications is that projecting fibers originating in the vlPAG release brain-derived neurotrophic factor (BDNF) in the RVLM (Yin et al, 2014). The BDNF is involved in plastic processes, such as neuronal proliferation and differentiation, leading to activity-dependent modifications in synapse physiology and structure (Korte et al, 1996;Liu et al, 2004;Malenka & Bear, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous research, a secondary and long-lasting mechanical allodynic and hyperalgesic response can be observed not only on the ipsilateral but also on the contralateral hind paw. Since sensory receptors in the bilateral area of secondary mechanical allodynia and hyperalgesia are unaffected, these sensory changes might be caused by central sensitization in the spinal cord and brain nucleus of the initial intense nociceptive discharge that follows the formalin injection (4)(5)(6). Various studies suggest that the release of immune substances and proinflammatory cytokines from spinal glia (7,8), and the bilateral signaling via commissural interneurons (9), might, in part, induce the mirror-image pain.…”
Section: Experimental Designmentioning
confidence: 99%